Ensaios sobre volatilidade: taxa de câmbio, investimento estrangeiro, governança corporativa e preços de ações - Carvalho, Luciano Ferreira (2014)
The thesis is divided in three essays on volatility. The first one investigates the exchange rate volatility and how this is related to the stock market price (IBOVESPA) volatility. The period of analysis is from 1999 to 2012 and it uses ARCH-GARCH, vector autoregressive (VAR) and error correction vector (VEC) models and two instruments of the VAR (Variance Decomposition Analysis and Impulse Response Function). Other than this, it was investigated the relation between disequilibrium in the exchange rate and the stock markets. The second essay analyzes capital flows volatility and their determinants. The main interest relies on the volatility of foreign investment in the stock market, extending the estimated volatilities for portfolio investment (PI), other investments (OI) and foreign direct investment (FDI). The empirical analysis on the volatility determinants is developed for four types of foreign investment. The sample uses monthly data starting in January 1999 until December 2012. It uses autoregressive conditioned to heteroskedasticity (ARCH / GARCH) models to measure the volatility. After this, the second essay estimates time series regressions using Ordinary Least Square (OLS) to investigate the relation between foreign investment volatility and its determinants. The goal of the third essay is to compare the stock market volatility for the companies that adopted good corporate governance practices with those that have not. It investigates the leverage and feedback effects. The sample includes Brazilian stocks from IBOVESPA from 2008 to 2012 using daily data. The essay estimates an ARCH-GARCH model to obtain the stock market volatilities and a TGARCH specification to investigate if stock market volatilities react in an asymmetric way to the stock return. Other than this, it estimates a multiple regression equation by OLS to investigate which one of the two effects (leverage or feedback) prevails.